2019
DOI: 10.1098/rsta.2019.0166
|View full text |Cite
|
Sign up to set email alerts
|

Neural network design for energy-autonomous artificial intelligence applications using temporal encoding

Abstract: Neural networks (NNs) are steering a new generation of artificial intelligence (AI) applications at the micro-edge. Examples include wireless sensors, wearables and cybernetic systems that collect data and process them to support real-world decisions and controls. For energy autonomy, these applications are typically powered by energy harvesters. As harvesters and other power sources which provide energy autonomy inevitably have power variations, the circuits need to robustly operate over a dynamic pow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…In case when the design parameters of the model are known, the forces can be determined by using formulas (13-15), as well as the moments acting on each wheel. Thus, the right-hand sides of the system of equations (5) are calculated. The set of equations (7-9, 13, 14) is a dynamic model of a robot with a drive in the form of two independent wheels.…”
Section: Simulating the Drive Systems Of Wheeled Robotmentioning
confidence: 99%
See 1 more Smart Citation
“…In case when the design parameters of the model are known, the forces can be determined by using formulas (13-15), as well as the moments acting on each wheel. Thus, the right-hand sides of the system of equations (5) are calculated. The set of equations (7-9, 13, 14) is a dynamic model of a robot with a drive in the form of two independent wheels.…”
Section: Simulating the Drive Systems Of Wheeled Robotmentioning
confidence: 99%
“…These forces must be taken into account when drilling the rotation of the developed wheeled robot on rubber mats mounted on the surface of the serviced space inside the animal unit. According to the studies of Mileiko, S., Bunnam, T., Xia, F., Shafik, R., Yakovlev, A., & Das, S. [5], it was found that the creation of artificial neural systems for applications of artificial intelligence requires considering physical parameters of a controlled object [5], in the role of which a wheeled robot acts as part of our research.…”
Section: Introductionmentioning
confidence: 99%
“…There are a lot of orientation methods, as well as components for these purposes, and to choose the optimal control method, one must proceed from the existing conditions. One of the field-acceptable methods of orientation in space is terrain mapping, which is an important component of the introduction of accurate farming methods [8]. Promising is the use of an autonomous control system based on laser scanners that can navigate the terrain in real time [9].…”
Section: Introductionmentioning
confidence: 99%